Using Extended Curriculum Programmes to Improve Student Success at Universities - Brits, Gideon P.; Eloff, Irma; Van Staden, Surette (International Journal of African Higher Education, 2025)
This study presents findings from a larger, mixed methods study that focuses on student success in an Academic Development Programme (ADP) at a South African university. Variables within the demographic, institutional, economic, cognitive, personal needs, and psychological domains of student success were investigated. A sequential triangulation research design was adopted. Data was collected in three phases: a quantitative, secondary analysis of existing, historical demographic data from students (n=5,560) in an Extended Curriculum Programme (ECP) during an 11–year period (2010–2020), a quantitative survey phase (n=161) and an interview phase (n=15). Data was analysed by means of descriptive statistics and theory-driven, inductive coding. The findings revealed that the ECP alleviates the differences in demography and economic status to such an extent that students from deprived areas were equally successful as students from more affluent backgrounds. While all domains are important, the study indicates that the psychological domain and the personal needs domain are most notable in relation to student success. The study recommends that Higher Education Institutions (HEIs) provide students with sufficient help and support especially on students’ mental well-being.